AldehydeAmine Chemistry Enables Tissue Adhesive Materials to Respond to Physiologic Variation and Pathologic States. Issue 9 (2nd October 2013) - Artzi, Natalie; Edelman, Elazer R.
Abstract Biomaterials science represents the next frontier in medical therapeutics. Innovations in materials design and formulation have helped create previously unimaginable interventions and composite devices with materials whose structure and function evolve with time. Yet, materials development has outstripped our ability to explain why, when, and how these materials work. Current characterization means are limited, especially for dynamic erodible materials that are specifically designed to fade away. This complexity and dynamism of emerging materials and the impact they have on tissue make it challenging to understand and predict material interactions with local tissues. Because tissuebiomaterials interactions are determined not only by the innate properties of the materials, but also by the local microenvironment at the implantation site, we must now examine the impact of target tissue site, state, and incidence of a disease on material performance, efficacy, and biocompatibility. This issue becomes increasingly important when considering surface interacting materials, whose intimate interactions with tissues are dictated by local mechanical forces, tissue target site, and the modulation of tissue surface properties manifested by specific disease types and states. The mechanisms involved and the extent to which these parameters affect the in vivo performance of materials are mostly unknown. These open questions motivated us to explore the determinant factors that affect the efficacy of materials, using adhesive materials whose surface interactions with tissues make them an ideal material class for the assessment of tissuematerial interactions. As an example of this paradigm, we determined how tissue amines served as a natural binding site for material aldehydes, enabling tissue‐specific binding that varied with natural changes in amine density from tissue to tissue and the physiologic environment, as well as with disease. The introduction of amines within the material also provides greater control over binding and material cohesion. This general mode will provide new tissue adhesives that can sense local tissue states and provide mechanical interactions titrated to context and need to enhance the desired effect and minimize local toxicity.